A study of reproductive morbidity of women in the Eastern Terai Region of Nepal - Dangal, Ganesh (Nepal Journal of Obstetrics and Gynaecology, 2008)
Aim: This study aims to fill the gap of information of reproductive health (RH) of women living in rural eastern Terai by providing baseline data on reproductive morbidity (RM) leading to pelvic organ prolapse (POP), reproductive tract infections (RTIs), menstrual problems and subfertility. Methods: This is a descriptive analysis of women who attended mobile RH camps in eastern Terai of Nepal organized at different villages falling in three districts namely Rautahat, Mahottari and Saptari during December 2005 and 2006. The diagnoses were made mostly on clinical evaluation and treatment provided. The leading reproductive morbidity of POP was dealt in detail and surgeries were performed in the district headquarters. The data were recorded and analysed manually. Analysis was done by standard statistical methods and a two tailed P value less than 0.05 was considered to indicate a significant difference. Results: Total number of women treated in the camps was 7750. Majority of the women in this study were found to be suffering from STI (30.1%), followed by POP (20.1%), menstrual disorders (16.7%) and subfertility (9.3%). Among POP patients majority received ring pessary insertion (43.8%) followed by counselling plus pelvic floor exercise (32.9%) and surgical correction (23.3%). Third-degree POP (38.6%) was commonest among all POP cases. Majority (60%) developed POP after first and second child birth. Conclusion: The major reproductive morbidity in this study was STI, POP (most of the women having thirddegree uterovaginal prolapse), menstrual disorders and sub-fertility. Surgical treatment at the camps could only be provided to small number, suggesting expansion of health services in rural Nepal by reproductive health barriers like poverty, education. Key words: menstrual disorders, pelvic organ prolapse, reproductive morbidity, reproductive tract infections, sub-fertility. doi:10.3126/njog.v3i1.1436 NJOG 2008 May-June; 3(1): 29 - 34